Inclusive and Digital Science Education—A Theoretical Framework for Lesson Planning - Laura Pannullo; Traugott Böttinger; Jan Winkelmann (Education Sciences)
The design of learning environments aimed at all students in the learning group is a requirement of modern lesson planning. In science education research, especially in the German tradition of didactics, the model of educational reconstruction (MER) is widely established for the planning of research programs and lesson planning. This model offers linking points in the conception of inclusive learning environments that have not yet been sufficiently considered. From an educational science perspective, Universal Design for Learning diclusive (UDL diclusive) provides a theoretical basis in the context of inclusive and digital lesson planning. In this paper, both MER and UDL diclusive are briefly presented. We argue for the combination of both frameworks for contemporary lesson planning. At the center of our considerations, we present possible points of linkage between the two frameworks. Connection points are illustrated by planning an inclusive and digital experiment-based physics lesson.